Practical problems on international contract regulation under the Peruvian Civil Code - Manrique de Lara Seminario, Jorge (2022)
This article covers some practical aspects of domestic contractual regulation under Peruvian Civil Code Chapter X. For this purpose, this article deals with some problematic aspects that could arise from the application of each one of the categories under article 2095 of Peruvian Civil Code, such as what is an applicable law, the place of performance of the contract and the place of subscription. In this context, this article covers the scope of what is an applicable law in contracts, some invalid agreement on applicable law, some problems related with the place of performance and the place of subscription of contracts.